Анализ случайности и степени гетерогенности временного ряда - Кондрашова, Н.В. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2010)
The statistical analysis of nonstationary series of world oil prices is carried out. The degree of heterogeneity is determined and the exact confidence intervals for the unknown theoretical frequency of change in the time series are obtained on the basis of its empirical distribution function and the methods of variation statistics.